Authentic Leadership and Fun Workplace Influence on Tourism Performance: The Mediating Role of Employee Engagement - Emi Wakhyuni; Siti Nurhayati; Fitri Rafianti; Kevin Tarigan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the influence of Authentic Leadership and Fun Workplace on the Performance of Tourism Industry Workers, by considering the role of Employee Engagement as a mediator. The location of the study was conducted in a certain area. The sample used in this study was 60 respondents. The data will be analyzed using statistical techniques such as path analysis to test the influence of independent variables on dependent variables through mediators. The results of the study indicate that based on direct testing, Authentic Leadership has a significant positive effect on Employee Engagement. Authentic Leadership has a significant positive effect on Tourism Industry Worker Performance. Employee Engagement has a significant positive effect on Tourism Industry Worker Performance. Fun Workplace has a significant positive effect on Employee Engagement. Fun Workplace has a significant positive effect on Tourism Industry Worker Performance. Based on the results of the mediation test, Authentic Leadership has a significant positive effect on Tourism Industry Worker Performance through Employee Engagement. Fun Workplace has a significant positive effect on Tourism Industry Worker Performance through Employee Engagement.